Facial Evaluation in Holoprosencephaly. Issue 1 (January 2017) - Pucciarelli, Valentina; Bertoli, Simona; Codari, Marina; Veggiotti, Pierangelo; Battezzati, Alberto; Sforza, Chiarella
Abstract : Abstract: Holoprosencephaly (HPE) is a malformation of the brain, occurring during the first weeks of pregnancy, that may be associated with several craniofacial alterations and different pathological conditions. The authors describe a 2-year-old girl with lobar HPE, epilepsy, but with a roughly normal face. Despite the macroscopic, clinical appearance, a facial morphometric analysis, performed through a stereophotogrammetric system, showed features that diverge from reference subjects and that are considered typical of HPE. This study highlights how a digital anthropometric facial assessment through stereophotogrammetry can be a useful and noninvasive instrument to investigate the facial features of HPE, especially in the presence of an apparently normal facial aspect. Additionally, it can provide the bases for future insights about the relationship between embryological facial and cerebral development, the time of the occurred defect and, in the end, enrich basic scientific knowledge.